The Influence Of Policies, Management Strategies, And Successful Project Performance On The Competitiveness Of Construction Service Companies - Saeful Prasetyo (Riwayat: Educational Journal of History and Humanities, 2023)
The government has spent quite a large budget on the infrastructure development sector, with this large budget for infrastructure development making business in the construction sector more promising, this has had an impact on increasing the number of companies implementing national construction services. The role of the government in adopting regulatory policies and laws for the implementation of construction services aims to provide direction for the growth and development of construction services. To face this intense competition, business actors need the creation of new strategies in the form of specific and adequate company management strategy patterns, successful Project performance is a measure of customer satisfaction, while customer satisfaction influences the competitiveness of a construction company. Data collection is carried out using a questionnaire technique which will be distributed and filled in by respondents from samples taken from the specified population. The simulation process uses the SPSS application for testing Validity, Reliability, Normality, Kolmogorov-Smirnov, Durbin-Watson, Liner Regression with T test, F test so that the equation of the influence of the independent variable on the dependent variable is found. The research results show that partial test results via the t-test, X1 (Policy), X2 (Management Strategy) and X3 (Project Performance Success) have an influence on (Y) Competitiveness of Construction Services Companies. Second, the test results based on the F test, can be concluded that the hypothesis is accepted, which means that policies, management strategies and successful project performance have a significant influence on the competitiveness of construction service companies. Third, management strategy factors are those that have the greatest influence on the competitiveness of construction service companies.